Understanding practices which foster inclusion: views from the top - de Largy, Christine; Anderson, Deirdre; Vinnicombe, Susan (Emerald, 2024)
Purpose This study aims to deepen our understanding of how inclusionary practices are used within organizations and how they satisfy specific inclusion needs. Design/methodology/approach We adopt a qualitative research design, reporting on data from semi-structured interviews conducted with 15 diversity and inclusion (D&I) directors/leads and using a thematic approach to analysis. Findings Our study expands understanding of inclusion practices, showing that they are not uniformly implemented and that practices may satisfy both needs to belong and differences valued, with interviewees prioritizing belonging. Well-being and career development are seen as important inclusion practices demonstrating support and appreciation of difference, thus as inputs, not outputs, of inclusion challenging existing assumptions. Inclusionary practices are malleable, and their impact depends critically on the leaders involved and their commitment to EDI. Originality/value Our study shows how practices satisfy inclusion needs and that the implementation of practices varies depending on the leaders involved.
Keywords: inclusive organization; inclusion practices; leadership; belonging; valuing uniqueness